Cooperative Treatment and Resource Utilization of Municipal Solid Waste by Industrial Coke Ovens: Effects of Doping Ratio and Management - Hongqing Ma; Jihua Zhao; Lv Pin; Hongzhi Ma; Jun Zhou; Jianguo Liu (BioResources, 2024)
For the collaborative treatment and resource utilization of an industrial coke oven on municipal solid waste (MSW), this study used MSW to prepare refuse-derived fuel (RDF). The influence of different mix ratio between RDF and coal on coking products was considered, and technical and economic analyses were conducted. The results showed that under the low mixture ratio (3%), the pyrolytic carbon obtained basically met the class III standard of metallurgical carbon. In the experiment of medium mixture ratio (25%, 30%, 35%), the product contained a certain amount of calorific value, lower than that of the metallurgical coke. It might be that the ash content increased, and such product can be used for civil coke or chemical coke. When the mixture ratio was 100%, the calorific value of pyrolysis carbon was 7.53 MJ/kg, representing 25.7% of the calorific value of ordinary coke. The gas production rate of the discharged gas was 0.35, and the calorific value is 14.0 MJ/kg, reaching 73.6% of the coke oven gas. Under the condition of no coal input, the MSW was converted into usable energy. The results demonstrated that coke oven pyrolysis with 100% RDF addition is the most feasible way to recycle resources and energy.